Nilai – Nilai Dakwah Dalam Kegiatan Niha’ie Di Ponpes Nurul – Qomar Palembang - Mahesa Mahesa; Aliasan Aliasan; Muslimin Muslimin (CV. ITTC INDONESIA, 2023)
This study discusses the values ​​of da'wah in niha'ie activities at the Nurul-Qomar Islamic Boarding School, Palembang. The aims of this research are to find out (1) What are the essential values ​​of da'wah in niha'ie activities at the Integrated Modern Islamic Boarding School Nurul - Qomar Palembang. (2) find out what are the Supporting and Inhibiting Factors in the Implementation of Niha'ie Activities at the Integrated Modern Islamic Boarding School Nurul - Qomar Palembang. The method used in this research is a qualitative approach with a descriptive approach. Data collection techniques used in this study were interviews, observation and recording. Data analysis used in this study is through data reduction, presentation and inference. This is shown from the results of this study, 1) The role in the formation of Islamic boarding school morale representing Ustad and Ustazza with students is going well. This includes activities such as: Prayers in Congregation of Imamah, Kitoba, Lectures, Amalia Tadris, Caring for Dead Body, Book Review, Autobiography, P2K (Public Service Practice), Nephew Nihaye's Final Examination. All male and female students of the Nurul Komal Islamic Boarding School participated in the activity. 2) Based on research conducted by researchers, researchers can conclude that: The role of Islamic boarding schools in building the spirit of students is good, and the activities of Ustaz and Ustaza have a positive impact on the spirit of students. can be improved from before. Even if there is support and disincentives for its implementation, there are supporting factors in student morale, namely the availability of proper facilities and infrastructure to facilitate activities and activities at Pompes, parents and their surroundings. Community support, and passion and enthusiasm is important. The cooperation between Ustaz and Ustaza in building good student enthusiasm can be reduced, but the inhibiting factor is the weather factor, which sometimes makes students lazy to go there, and students still lack confidence and stability in participating. This creates a certain feeling of laziness among students. students participating in activities at Islamic boarding schools.